'Slowing down' in small and medium-sized towns: Cittaslow in Germany and Italy from a social innovation perspective. Issue 1 (1st January 2021) - Sept, Ariane
ABSTRACT: Smaller towns in rural regions are important anchors for regional development, but they are not usually considered particularly innovative and open to new ideas. This paper asks how the network of small and medium-sized towns, Cittaslow, could establish slowing down as something new in local development. Against the theoretical background of sociological innovation research, an analytical framework of social innovation is elaborated to analyse Cittaslow using four case studies: two German and two Italian towns. Based on fieldwork in the four towns, this paper shows that discourse and communication on slowing down, local projects labelled as slow and new cooperation structures go hand in hand. This leads to the conclusion that new ways of local development need a communicative umbrella under which projects and stakeholders come together. The paper furthermore demonstrates that the analytical framework, with its triad of semantics, pragmatics and grammar, is extremely helpful for analysing spatial development and has the potential to be adapted as a tool for policy strategies.